Tales of three budgets: Changes in long-term fiscal projections through the GFC and beyond - Matthew Bell; Paul Rodway (New Zealand Government, The Treasury, 2013)
This paper examines fiscal projections based on three consecutive budget forecasts (2009-2011) and provides cautionary insights as to how these projections only a year or two apart can lead to dramatic differences in projected debt levels in the future. Projections of net debt from a Budget 2011 forecast base are much lower, by 2050, than those for Budget 2009. This is largely due to the Budget 2011 forecast base having lower expenditure and higher revenue than the forecast base of the Budget 2009 projections. The paper also underscores how short-term policy changes, if sustained, can make a big difference over the long term and how, over time, the more fundamental structural factors such as demographics can prove to be more durable in influencing fiscal sustainability. Finally, it argues that, even though the level of debt-to-GDP shifts by mid-century, the messages we take from these projections remain the same: spending and possibly tax policies need to change, if we are to avoid passing debt that generates little social return onto our descendants, and early changes alleviate the need for more drastic revisions in the future.
Keywords: H69; H51; H55; 330; Long-term fiscal projections; Fiscal sustainability